1982
DOI: 10.1128/mcb.2.11.1331
|View full text |Cite
|
Sign up to set email alerts
|

Sequence comparison in the crossover region of an oncogenic avian retrovirus recombinant and its nononcogenic parent: genetic regions that control growth rate and oncogenic potential.

Abstract: NTRE 7 is an avian retrovirus recombinant of the endogenous nononcogenic Rous-associated virus-0 (RAV-0) and the oncogenic, exogenous, transformationdefective (td) Prague strain of Rous sarcoma virus B (td-PrRSV-B). Oligonucleotide mapping had shown that the recombinant virus is indistinguishable from its RAV-0 parent except for the 3'-end sequences, which were derived from tdPrRSV-B. However, the virus exhibits properties which are typical of an exogenous virus: it grows to high titers in tissue culture, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 44 publications
1
51
0
Order By: Relevance
“…Early studies with RSV found that viral sequences immediately preceding the 3Ј LTR of the Prague (PrRSV) and Schmidt-Ruppin strains of RSV (SR RSV) enhanced reporter gene expression (18,20). Interestingly, the enhancer domain in PrRSV, termed the exogenous virus-specific region (XSR) (18), was shown to be responsible for differences in oncogenicity (36), and the same region of the avian leukosis virus, subgroup J (ALV-J), termed E, has been shown to contribute to oncogenicity in certain genetic lines of chickens, potentially through an enhancing mechanism (3).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies with RSV found that viral sequences immediately preceding the 3Ј LTR of the Prague (PrRSV) and Schmidt-Ruppin strains of RSV (SR RSV) enhanced reporter gene expression (18,20). Interestingly, the enhancer domain in PrRSV, termed the exogenous virus-specific region (XSR) (18), was shown to be responsible for differences in oncogenicity (36), and the same region of the avian leukosis virus, subgroup J (ALV-J), termed E, has been shown to contribute to oncogenicity in certain genetic lines of chickens, potentially through an enhancing mechanism (3).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, RAV-0 becomes oncogenic when its own U3 region is replaced by that of RSV (Robinson et al, 1982;Tsichlis et al, 1982). Furthermore, it has been demonstrated that the LTR of a tumorigenic retrovirus (RAV-2) gives rise to a 10-fold higher level of env gene transcription than the RAV-0 LTR (Cullen et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Since RAV-0 is an endogenous virus which also has the ability to multiply in avian cells, it might be that the loss of enhancer activity evolved to reduce oncogenicity without losing viability. Robinson et al (1982) and Tsichlis et al (1982) have demonstrated that replacing the U3 region of the RAV-0 LTR with the homologous region of td-RSV restores oncogenicity in vivo. Thus, the U3 region determines the potential of a virus to induce malignant diseases such as lymphomas, carcinomas, chondrosarcomas, fibrosarcomas and osteopetrosis Robinson et al, 1982).…”
Section: Selection Of Enhancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, oncogene activation and neoplastic disease can also follow the chromosomal integration of a nonacute transforming retrovirus near these potentially transforming host genes. The major retroviral sequences necessary for transformation in avian leukosis virus have been localized to the U3 region of retroviral long terminal repeats (LTRs) (21,22,(31)(32)(33). Recent studies with murine nontransforming retroviruses also argue for the importance of the proviral LTR sequences in determining oncogenicity (3,6,15).…”
mentioning
confidence: 99%